SNAP Participants and High Levels of Food Insecurity in the Early Stages of the COVID-19 Pandemic. (July 2021) - Siddiqi, Sameer M.; Cantor, Jonathan; Dastidar, Madhumita Ghosh; Beckman, Robin; Richardson, Andrea S.; Baird, Matthew D.; Dubowitz, Tamara
Objectives: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately strained households experiencing poverty, particularly Black and Latino households. Food insecurity, which entails having limited or uncertain access to a sufficient quantity of nutritious food, is a key pandemic-related consequence. We examined how people enrolled in the Supplemental Nutrition Assistance Program (SNAP) have been affected by the pandemic, particularly Black participants and participants residing in food deserts. Methods: Using survey data from a longitudinal cohort study of predominantly Black low-income adults aged ≥18 residing in urban food deserts in Pittsburgh, Pennsylvania, we examined changes in food insecurity and SNAP participation before COVID-19 (2018) and early in the COVID-19 pandemic (March–May 2020). We modeled changes in food insecurity from 2018 to 2020 via covariate-adjusted logistic regression. Results: Food insecurity increased significantly among participants enrolled in SNAP and surveyed in both 2018 and 2020 (from 25.9% in 2018 to 46.9% in 2020; P < .001). Compared with cohort participants not enrolled in SNAP at both points, cohort participants enrolled in SNAP in 2018 and 2020 had the highest rates of using a food bank in 2020 (44.4%) and being newly food insecure in 2020 (28.9%) (ie, they were food insecure in 2020 but not in 2018). Conclusions: Food insecurity during the COVID-19 pandemic increased among low-income Black households enrolled in SNAP and residing in a food desert. Public health recovery efforts might focus on modifying SNAP to improve the food security of people experiencing poverty.